Experimental evaluation of the image quality and dose in digital mammography: Influence of x-ray spectrum. (November 2015) - Tomal, A.; Perez, A.M.M.M; Silva, M.C.; Poletti, M.E.
Abstract: In this work, we studied experimentally the influence of x-ray spectrum on the contrast-to-noise ratio (CNR) and the average glandular dose (MDG) for two digital mammography systems: Senographe 2000D (GE Medical Systems) and Lorad Selenia (Hologic), with indirect and direct detector imaging technology, respectively. CNR and MGD were determined using PMMA phantoms simulating breasts with thicknesses of 4 cm and 6 cm. All available anode/filter combinations of the systems were evaluated for a wide range of tube voltages values. Results indicated that the Rh/Rh combination provides the highest image quality with the lower mean glandular dose for the Senographe 2000D system. For the Lorad Selenia system, the W/Ag combination at 30 kV showed the best performance, in terms of dose saving and image quality improvement in relation to all tube voltage range. The comparison between the optimal x-ray spectra and those selected by the AEC mode showed that this automatic selection mechanism could be readjusted to optimize the relationship between image quality and dose. Abstract : Highlights: CNR and MGD were studied for different x-ray spectra in two mammographic systems. The optimum x-ray spectrum for each system was determined using a FOM. The results were compared with those obtained using the AEC mode AEC mechanism could be readjusted to optimize the relationship between CNR and MGD.